Establishment and capacity analysis of the platelet donor database with HPA and HLA genotype in Nanjing - LIU Taixiang; MA Ling; LIANG Wenbiao; JIANG Nizhen; LI Ling (Zhongguo shuxue zazhi)
Objective To establish a known HPA/HLA genotype platelet donor database in Nanjing, analyze the polymorphism of HPA-1~6w, -15 and HLA-A, -B and evaluate the matching probability and appropriate capacity of the database for platelet matching transfusion. Methods HPA-1~6w, -15 and HLA-A, -B were genotyped by PCR-SSP and PCR-SBT, respectively. The allele frequency and haplotype frequency of HPA-1~6w, -15 and HLA-A,- B were calculated with SHEsis software, and then the matching probability and appropriate capacity were obtained according to the haplotype frequencies. Results The population genetic polymorphisms data of HPA-1~6w, -15 and HLA-A, -B in Nanjing were obtained. According to the subsequent calculating, without considering ABO blood type, in a database size of 527 donors, a patient with haplotype frequency >0.001 has approximate 95% probability to achieve matching of HPA-1~6w, -15 genotype. A database with a total size of 1 875 donors can afford the patient with haplotype frequency >0.001 to find at least 1 HLA-A, -B matched donor in 95% probability. Conclusion We established a local platelet donor database with known HPA and HLA genotype, which also provided important data support for the subsequent construction, maintenance and clinical application of the database.